An Existence of State Administration Court in Establishing Good Governance - Ruslin Ruslin (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
Administration officials have broad authority in carrying out the affair of government. With this broad authority tends to be misused to cause harm and injustice in the society, therefore there must be other institutions that control it. Based on the theory of Trigs Politico executive agencies are politically controlled by the legislative and juridical institutions controlled by the judiciary, because the officials running the state administration executive functions that control the judiciary is legally the state administrative court. Judicial control of administrative functions of the state administrative court in addition aims to provide legal protection for the public and state administration officials themselves, as well as state administrative law enforcement agencies who aspire to realize a good and authoritative government. Keywords: Good government, State administration court